Estación Biológica Quebrada Blanco: A little known site for research in biodiversity and ecology in Peruvian Amazonia - Heymann, Eckhard W. (2021)
The Estación Biológica Quebrada Blanco (EBQB) in north-eastern Peruvian Amazonia is a place where research has been conducted since 1984; mainly, on the ecology and behavior of primates, but, later inventories were realized for trees (>10 cm dbh), ferns and birds. The EBQB area is very little disturbed and located in a region of high biodiversity. Here we describe the history of EBQB, summarize the available information on its biodiversity and point out the potential of EBQB for future studies on the biodiversity and ecology of a broad spectrum of organisms.